Pola Komunikasi Penggemar Dengan Idola K-Pop Melalui Media Sosial Weverese - Siti Maesyaroh,, Syarah; Annisa, Nurin; Yuniar, Listia (Jurnal Syntax Fusion, 2024)
The K-Pop phenomenon has changed the communication patterns between idols and fans through specialized social media platforms like Weverse. This study aims to analyze the communication patterns formed between fans and K-Pop idols through the Weverse platform. The study used a qualitative approach with a content analysis method to communication activities on Weverse for one month, including live streaming features, comment and reply systems, and Artist Posts. The results of the study showed that communication on Weverse has multidimensional characteristics that combine vertical interaction between idol-fans and horizontal interaction between fans. Live streaming generates informative, emotional-expressive, and performative responses with a systematic comment selection pattern. The platform manages to create the illusion of closeness through everyday content and direct greetings, but accessibility remains strategically controlled. The main findings confirm the transformation of parasocial relationships in the digital age into hybrid parasocial relationships that have real interactivity elements but remain asymmetrical. This research makes a theoretical contribution to the understanding of the evolution of mass communication towards a hybrid form of communication that combines elements of broadcasting, interpersonal communication, and community interaction in a digital ecosystem.